Mechanism of dual specificity kinase activity of DYRK1A. (22nd July 2013) - Walte, Agnes; Rüben, Katharina; Birner‐Gruenberger, Ruth; Preisinger, Christian; Bamberg‐Lemper, Simone; Hilz, Nikolaus; Bracher, Franz; Becker, Walter
Abstract : The function of many protein kinases is controlled by the phosphorylation of a critical tyrosine residue in the activation loop. Dual specificity tyrosine‐phosphorylation‐regulated kinases (DYRKs) autophosphorylate on this tyrosine residue but phosphorylate substrates on aliphatic amino acids. This study addresses the mechanism of dual specificity kinase activity in DYRK1A and related kinases. Tyrosine autophosphorylation of DYRK1A occurred rapidly during in vitro translation and did not depend on the non‐catalytic domains or other proteins. Expression in bacteria as well as in mammalian cells revealed that tyrosine kinase activity of DYRK1A is not restricted to the co‐translational autophosphorylation in the activation loop. Moreover, mature DYRK1A was still capable of tyrosine autophosphorylation. Point mutants of DYRK1A and DYRK2 lacking the activation loop tyrosine showed enhanced tyrosine kinase activity. A series of structurally diverse DYRK1A inhibitors was used to pharmacologically distinguish different conformational states of the catalytic domain that are hypothesized to account for the dual specificity kinase activity. All tested compounds inhibited substrate phosphorylation with higher potency than autophosphorylation but none of the tested inhibitors differentially inhibited threonine and tyrosine kinase activity. Finally, the related cyclin‐dependent kinase‐like kinases (CLKs), which lack the activation loop tyrosine, autophosphorylated on tyrosine both in vitro and in living cells. We propose a model of DYRK autoactivation in which tyrosine autophosphorylation in the activation loop stabilizes a conformation of the catalytic domain with enhanced serine/threonine kinase activity without disabling tyrosine phosphorylation. The mechanism of dual specificity kinase activity probably applies to related serine/threonine kinases that depend on tyrosine autophosphorylation for maturation. Structured digital abstract: CLK1 and CLK1 phosphorylate by protein kinase assay (View interaction) HIPK2 and HIPK2 phosphorylate by protein kinase assay (View interaction) DYRK1A phosphorylates SF3B1 by protein kinase assay (View interaction) DYRK1A and DYRK1A phosphorylate by protein kinase assay (View interaction) Abstract : This study addresses the mechanism of dual specificity kinase activity in DYRK1A and related kinases. Here, present results that support a model of DYRK autoactivation in which the one‐time tyrosine autophosphorylation in the activation loop stabilizes a conformation of the catalytic domain with enhanced serine/threonine kinase activity without disabling tyrosine phosphorylation by the mature kinase.